“Projeto Canarana” : trajetória de famílias em busca de terras em Mato Grosso (1972-1981) - Moraes, Adriano Knippelberg de (2015)
We studying the territorial transformations occurred in North Central during the civil-military period (1964-1981), more precisely the Colonization Project Canarana I, who came to be developed in Mato Grosso city of Barra do Garças in 1972. This project was planned and executed by the Cooperative of Colonization March 31 LTDA (COOPERCOL), which brought together small farmers Tenente Portela, in Rio Grande do Sul and helped them to migrate to the Mato Grosso. This project and others that have been deployed in the Legal Amazon, were only possible due to the creation of a set of laws and credit lines that favored those who wished to "enter the empty immensity" of Brazil.